2014
DOI: 10.1186/s12916-014-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antenatal dietary and lifestyle advice for women who are overweight or obese on maternal diet and physical activity: the LIMIT randomised trial

Abstract: BackgroundOverweight and obesity is a significant health concern during pregnancy. Our aim was to investigate the effect of providing antenatal dietary and lifestyle advice to women who are overweight or obese on components of maternal diet and physical activity.MethodsWe conducted a randomised controlled trial, in which pregnant women with a body mass index ≥25 kg/m2, and singleton gestation between 10+0 to 20+0 weeks were recruited and randomised to Lifestyle Advice (involving a comprehensive dietary and lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
182
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(206 citation statements)
references
References 71 publications
20
182
4
Order By: Relevance
“…Recent intervention trials have successfully increased physical activity levels among obese pregnant women (Dodd et al, 2014;Poston et al, 2015). However, similar to the women in this study, others have identified a lack of advice and support with physical activity in pregnancy, and a particular concern around safety (Weir et al, 2010;Sui and Dodd, 2013;Padmanabhan et al, 2015), while receiving physical activity advice from health professionals is a key enabler to supporting physical activity (Sui and Dodd, 2013).…”
Section: Resultsmentioning
confidence: 51%
“…Recent intervention trials have successfully increased physical activity levels among obese pregnant women (Dodd et al, 2014;Poston et al, 2015). However, similar to the women in this study, others have identified a lack of advice and support with physical activity in pregnancy, and a particular concern around safety (Weir et al, 2010;Sui and Dodd, 2013;Padmanabhan et al, 2015), while receiving physical activity advice from health professionals is a key enabler to supporting physical activity (Sui and Dodd, 2013).…”
Section: Resultsmentioning
confidence: 51%
“…In that survey, eating sufficient vegetables and fruit was the most frequently cited component of a healthy diet, followed by limiting fat intake, which is consistent with what our study showed for Australians during January and February. However, lack of knowledge around the health consequences of poor weight management, healthy eating, and safe exercise have been identified as barriers to weight management in other studies, such as a study of pregnant women who paradoxically had access to freely provided weight loss information (Sui et al, 2013;Dodd et al, 2014), suggesting a possible mismatch between what they required and what was supplied.…”
Section: Discussionmentioning
confidence: 99%
“…The LIMIT trial from Australia (Dodd et al, 2014b) which recruited over 2000 overweight or obese women found that a lifestyle intervention which focused on diet and physical activity was associated with a reduction in number of macrosomic babies born to women allocated to the intervention, but as this was a prespecified secondary outcome, a chance finding cannot be ruled out. Reasons postulated for this difference included greater physical activity in the intervention arm and differences in dietary intake including a reduction in energy intake from saturated fat and an increase in dietary fibre (Dodd et al, 2014a). The results of recently completed trials of pregnancy weight management interventions in the UK are currently awaited.…”
mentioning
confidence: 97%